2016
DOI: 10.31983/jkg.v3i2.1778
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dental Braille Education (Dbe) Terhadap Oral Hygiene Pada Anak Tunanetra

Abstract: TITLEThe influence of dental braille education (DBE) to oral hygiene of blind childrenABSTRACTBlind children has poor oral hygiene. Such condition due to tooth brushing is not monitored, other factors such as brushing technique, motor skills and mentoring assistance are still negligible. Besides the lack of visualization to understand and master the techniques of oral hygiene practices. This study aimed to analyze the influence of Braille Dental Education (DBE) against Oral Hygiene in blind children.Pre-experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…As Foster suggests, behavioral change can be evaluated after 21 days. 17 In terms of the difference in effectiveness between Braille-verbal and tactile-verbal tooth-brushing exercise methods, this study's conclusion was consistent with that of a study by Sabilillah et al 18 who concluded that Dental Braille Education could change blind children's knowledge and attitude. This finding, it is suggested, could be related to Braille text and reading aloud technique in educating blind students.…”
Section: Discussionsupporting
confidence: 89%
“…As Foster suggests, behavioral change can be evaluated after 21 days. 17 In terms of the difference in effectiveness between Braille-verbal and tactile-verbal tooth-brushing exercise methods, this study's conclusion was consistent with that of a study by Sabilillah et al 18 who concluded that Dental Braille Education could change blind children's knowledge and attitude. This finding, it is suggested, could be related to Braille text and reading aloud technique in educating blind students.…”
Section: Discussionsupporting
confidence: 89%
“…Penelitian yang dilakukan oleh singh dkk. pada tahun 2014, menunjukkan buruknya status kesehatan gigi dan mulut pada anak berkebutuhan khusus disebabkan oleh kurangnya pemahaman dan penguasaan mengenai teknik praktik kebersihan gigi dan mulut (Sabilillah et al, 2016). I Gede Dewa berdasarkan penelitianya memberikan saran bahwa penyakit gigi dan mulut seperti karies yang diakibatkan oleh kurangnya kebersihan gigi dan mulut dapat dicegah dengan dilakukanya penyuluhan kesehatan gigi (Prasada, 2016).…”
Section: Pendahuluanunclassified
“…[5] India has the highest percentage of caries among blind individuals globally-60%. [6] On the other hand, dental caries is more common than 80.6% in Indonesia. [6] Fifty percent of the visually impaired individuals in Indonesia have an Oral Hygiene Index Score (OHI-S) that falls within the medium range, specifically with an average score of 2.3.…”
Section: Introductionmentioning
confidence: 99%
“…[6] On the other hand, dental caries is more common than 80.6% in Indonesia. [6] Fifty percent of the visually impaired individuals in Indonesia have an Oral Hygiene Index Score (OHI-S) that falls within the medium range, specifically with an average score of 2.3. [6] The factors contributing to oral health issues in blind individuals include the use of cariogenic foods, the structure of their teeth, and a lack of dental health education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation